The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biom12060767
|View full text |Cite
|
Sign up to set email alerts
|

Gut Steroids and Microbiota: Effect of Gonadectomy and Sex

Abstract: Sex steroids, derived mainly from gonads, can shape microbiota composition; however, the impact of gonadectomy and sex on steroid production in the gut (i.e., gut steroids), and its interaction with microbiota composition, needs to be clarified. In this study, steroid environment and gut steroidogenesis were analysed by liquid chromatography tandem mass spectrometry and expression analyses. Gut microbiota composition as branched- and short-chain fatty acids were determined by 16S rRNA gene sequence analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…While an “optimal microbiome” has not been defined, considering the influence of numerous intrinsic and environmental factors, a healthy state has previously been characterized as the absence of any disease ( Aagaard et al., 2013 ). The microbiome changes dramatically as the host ages, while also being influenced by host genetics and sex ( Haro et al., 2016b ; Badal et al., 2020 ; Caputi et al., 2022 ; Diviccaro et al., 2022 ). Also, it is commonly appreciated that the microbiome is readily impacted by lifestyle factors such as diet and exercise ( Sandhu et al., 2017 ; Zmora et al., 2019 ; Berding et al., 2021 ).…”
Section: The Microbiomementioning
confidence: 99%
“…While an “optimal microbiome” has not been defined, considering the influence of numerous intrinsic and environmental factors, a healthy state has previously been characterized as the absence of any disease ( Aagaard et al., 2013 ). The microbiome changes dramatically as the host ages, while also being influenced by host genetics and sex ( Haro et al., 2016b ; Badal et al., 2020 ; Caputi et al., 2022 ; Diviccaro et al., 2022 ). Also, it is commonly appreciated that the microbiome is readily impacted by lifestyle factors such as diet and exercise ( Sandhu et al., 2017 ; Zmora et al., 2019 ; Berding et al., 2021 ).…”
Section: The Microbiomementioning
confidence: 99%
“…For instance, levels of testosterone, dihydroxyprogesterone, and allopregnanolone positively correlate with levels of Blautia; whereas, those of testosterone, allopregnanolone, pregnanolone, progesterone, and dihydroxyprogesterone negatively correlate with levels of Roseburia. 60 The administration of oral contraceptives fails to alter the overall composition of gut microbiome in healthy women. 61 However, dietary changes affect microbial communities in the gut in terms of both composition and function, which may influence innate and adaptive immune systems of the host.…”
Section: Gut Microbiome and Changes In Its Composition With Menstrual...mentioning
confidence: 99%
“…For instance, levels of testosterone, dihydroxyprogesterone, and allopregnanolone positively correlate with levels of Blautia ; whereas, those of testosterone, allopregnanolone, pregnanolone, progesterone, and dihydroxyprogesterone negatively correlate with levels of Roseburia . 60 …”
Section: Gut Microbiome and Changes In Its Composition With Menstrual...mentioning
confidence: 99%
“…The microbiome has been shown to impact gamete development, including spermatogenesis and oogenesis. Specifically, studies in mice have demonstrated that the gut microbiome is capable of influencing the expression of genes related to spermatogenesis and steroidogenesis ( Ding et al 2020 , Diviccaro et al 2022 ). This interplay may affect hormone levels and reproductive outcomes.…”
Section: ‘Reproductive’ Microbiomesmentioning
confidence: 99%